Enhanced piezoelectric performance in Na0.5Bi4.5Ti4O15‐based bismuth‐layered ceramics by Nb/Mn doping modification. Issue 4 (25th December 2022) - Mo, Wen; Luo, Xin; Zhang, Yangyang; Niu, Huiyan; Fang, Ziyan; Hu, Liangwei; Liu, Kun; Li, Qifan; Chen, Yong; Shen, Meng
Abstract: In this work, Na0.5 Bi4.5 Ti3.94– x Mn0.06 Nb x O15+ y bismuth‐layered ferroelectric ceramics were prepared by a solid‐state reaction method. The effect of Nb 5+ content on crystal morphology, electrical properties, and piezoelectric performance were systematically investigated. The results show that the introduction of Nb 5+ into Na0.5 Bi4.5 Ti3.94– x Mn0.06 Nb x O15+ y ceramics to replace Ti 4+ increases the ratio of b / a lattice parameter, leading to the TiO6 octahedral distortion and the structural transformation tendency from the orthorhombic to tetragonal phase, which facilitates dipole movements of Na0.5 Bi4.5 Ti3.94– x Mn0.06 Nb x O15+ y ceramics. Therefore, the ferroelectric properties of Na0.5 Bi4.5 Ti3.94– x Mn0.06 Nb x O15+ y ceramics are improved, and an enhanced piezoelectric coefficient of 30 pC/N combining great temperature stability with d 33 value higher than 25 pC/N in the temperature range of 25°C–450°C has been realized in Na0.5 Bi4.5 Ti3.94– x Mn0.06 Nb x O15+ y ceramics with x  = 0.08 mol. Our work provides a good model for designing lead‐free ultrahigh Curie temperature piezoelectric devices that can be practically applied in extremely harsh environments.